When Memory is Cross-Cultural Translation: Eva Hoffman’s Schizophrenic Autobiography - Ingram, Susan (TTR, 1996)
AbstractWhen Memory is Cross-Cultural Translation: Eva Hoffman's Schizophrenic Autobiography — This article approaches the question of what happens when the text to be translated or rewritten as a result of cross-cultural experience is the self — how is the resulting autobiography to be read? Its answer takes the form of the theorizing of Deleuze and Guattari. It is contended that the potentiality characterizing the position of linguistic alterity experienced by bilingual authors, such as Hoffman, is the underlying assumption in Deleuze and Guattari's work. By identifying the connections between schizophrenia and minor literature and by delineating minor from minority literature, one can better understand the dynamics necessitating self-translation and the forms which cross-cultural writing can take.